2017
DOI: 10.1038/s41598-017-11616-z
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics of nanodisc formation mediated by styrene/maleic acid (2:1) copolymer

Abstract: Styrene/maleic acid copolymers (SMA) have recently attracted great interest for in vitro studies of membrane proteins, as they self-insert into and fragment biological membranes to form polymer-bounded nanodiscs that provide a native-like lipid-bilayer environment. SMA copolymers are available in different styrene/maleic acid ratios and chain lengths and, thus, possess different charge densities, hydrophobicities, and solubilisation properties. Here, we studied the equilibrium solubilisation properties of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
107
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 75 publications
(128 citation statements)
references
References 31 publications
21
107
0
Order By: Relevance
“…In addition we found that SZ30010 also affords the improved purity observed with SMA2000. Despite having small differences in average size and ratio of styrene:maleic acid, the particles produced using SMA2000 and SZ30010 were very similar in size at just under 10 nm diameter, which agrees well with previous reports using these two polymers [3,17,24,25].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In addition we found that SZ30010 also affords the improved purity observed with SMA2000. Despite having small differences in average size and ratio of styrene:maleic acid, the particles produced using SMA2000 and SZ30010 were very similar in size at just under 10 nm diameter, which agrees well with previous reports using these two polymers [3,17,24,25].…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies on the thermodynamics of phospholipid solubilisation by SMA2000 [27] and SZ30010 [24] indicate that these polymers have similar thermodynamic efficiencies. SMA2000 exhibits a larger negative free energy change associated with the polymer, indicating it is more efficient at solubilising phospholipids.…”
Section: Discussionmentioning
confidence: 95%
“…To ensure complete solubilization of the MLVs, a ratio of 0.5 ([SMA]/[lipid]) was used that is above the reported Rsol value (ratio above which the liposome solubilization is complete) for POPC liposomes [44]. To ensure complete solubilization of the MLVs, a ratio of 0.5 ([SMA]/[lipid]) was used that is above the reported Rsol value (ratio above which the liposome solubilization is complete) for POPC liposomes [44].…”
Section: Electrophysiologymentioning
confidence: 99%
“…Styrene maleic acid lipid particles were prepared by incubating MLVs (1.3 mM) with SMA solution (6.5 mM) both in PBS. To ensure complete solubilization of the MLVs, a ratio of 0.5 ([SMA]/[lipid]) was used that is above the reported Rsol value (ratio above which the liposome solubilization is complete) for POPC liposomes [44]. Formation of SMALPs was followed by Dynamic Light Scattering (Vasco, Cordouan) and also by MDS (microfluidic diffusional sizing; in this case, we have included 10% palmitoyl-oleoyl-phosphatidylserine in the lipid system in order to have a reactive primary amine for fluorescent labeling).…”
Section: Preparation Of Small Unilamellar Vesicles Large Unilamellarmentioning
confidence: 99%
“…The most hydrophilic SMA is 1.4:1 and the most hydrophobic is 4:1. The potential of these polymers to solubilise different membrane proteins has been assessed with the most promising SMA variant bearing a styrene to maleic acid ratio of 2:1 (50). SMA with a 3:1 ratio has comparable efficiency to insert into membranes and both co-polymers display average M w in the range of 7.5-10kDa.…”
Section: Styrene Maleic Acid Lipid Particles (Smalps)mentioning
confidence: 99%